2020
DOI: 10.3389/fvets.2020.00347
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Use of Amniotic Microvesicles for Regenerative Medicine Treatment of a Mare With Chronic Endometritis

Abstract: Chronic endometritis is an inflammation in the inner layer of uterine mucosa, with or without an infectious process, which affects the animal's fertility but not its general health. A variety of treatments has been adopted over the years but to date, no effective cures have been able to renew the injured tissue. Since the defects in the fetal-maternal communication are caused by degenerative changes due to chronic endometrial inflammation, our working hypothesis was a new approach to this disease by the regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Therefore, the exchange of EVs cargo between cells favors cell-cell communication and regulation of the immune response [ 15 ]. Inflammation of the inner layer of uterine tissues, either due to an infectious agents (bacteria& fungi) or non-infectious agents (trauma& sperm) is the main cause of sub-fertility in mares [ 24 , 38 ]. The successful resolution of inflammation is a critical step to maintain uterine homeostasis and subsequently provide the optimum milieu for the embryonic development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exchange of EVs cargo between cells favors cell-cell communication and regulation of the immune response [ 15 ]. Inflammation of the inner layer of uterine tissues, either due to an infectious agents (bacteria& fungi) or non-infectious agents (trauma& sperm) is the main cause of sub-fertility in mares [ 24 , 38 ]. The successful resolution of inflammation is a critical step to maintain uterine homeostasis and subsequently provide the optimum milieu for the embryonic development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, their ability to promote re-epithelialization of skin wounds and stroke recovery has been reported [178]. Recently, amniotic derived EVs were used to treat endometritis in mare with the goal of achieving successful pregnancy [179]. This mare was an 11-year-old Friesian, with a history of failed pregnancies despite numerous insemination attempts for many years.…”
Section: Evs and Therapeutic Actionmentioning
confidence: 99%
“…Extracellular vesicles can be administered via intravenous, subcutaneous, intraperitoneal, oral, and intranasal routes to reach the desired in vivo target sites, depending on the intended therapeutic action and tissues to be targeted [180]. In the paper by Lange-Consiglio et al [179] EVs were administered by the intravaginal rout. The biodistribution and targeting potential of EVs is dependent on EV sizes, surface markers, and their isolation methods.…”
Section: Evs and Therapeutic Actionmentioning
confidence: 99%
“…As a mechanism of intercellular communication, MVs can transfer molecules such as DNA, mRNA, and miR from their origin cells to receptor cells (Lange‐Consiglio et al, 2020; G. Qiu et al, 2018). Ward et al (2018) have also shown that BMSCs‐MVs carry effective angiogenic cytokines and mRNA molecules to affect the local environment.…”
Section: Discussionmentioning
confidence: 99%